2016
DOI: 10.1016/j.aott.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patient training on persistence, compliance, and tolerability of different dosing frequency regimens of bisphosphonate therapy: An observational study in Turkish patients with postmenopausal osteoporosis

Abstract: ObjectiveIn our study, we aimed to evaluate the influence of training on compliance and persistence with bisphosphonate treatment given on a weekly vs. monthly basis in postmenopausal osteoporosis patients.MethodsA total of 979 patients with postmenopausal osteoporosis (mean age: 63.2 ± 7.2 years) were included in this national, multicenter, prospective non-interventional observational cohort registry study. Patients were randomized into training (n = 492, 50.3%, mean age: 63.4 ± 7.2 years) and control (n = 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…However, the monthly dose was associated with a significantly higher compliance rate. Many studies, including ours, supported the fact that compliance with the monthly dose was higher than that for the weekly dose [ 21 , 26 , 27 , 31 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the monthly dose was associated with a significantly higher compliance rate. Many studies, including ours, supported the fact that compliance with the monthly dose was higher than that for the weekly dose [ 21 , 26 , 27 , 31 ].…”
Section: Discussionmentioning
confidence: 73%
“…The comparison of weekly versus monthly doses also showed an improved MPR with extended dosing intervals, [ 26 , 27 ] but the difference was not large and was occasionally controversial. USA military data showed that the overall rates of compliant patients (the ratio of MPR ≥ 80%) on weekly and monthly doses were 42.2% and 45.7%, respectively, for 1 year [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not find significant differences between the training and control groups in terms of compliance and persistence. The patients on the monthly bisphosphonate regimen showed significantly longer persistence in comparison to patients on the weekly regimen [22].…”
Section: Telephone Calls Emails Educational Meetingsmentioning
confidence: 87%
“…Most of the studies evaluating adherence to and persistence in osteoporosis treatment are based on patient education, using different methods. The use of telephone calls, emails, and alarm clocks as a reminder to take medication as prescribed compared with the usual care pathways seems not to improve adherence and persistence [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 98%
“…It was reported one-year compliance was lower than 25% in all osteoporosis therapies, leaving patients with higher risk for fractures and public health costs. [7] Among the antiresorptive osteoporosis drugs, there are numerus studies on compliance of BP, [8][9][10][11][12][13][14] whereas, there are relatively few studies on compliance of SERM. [3,15,16] The primary objective of this study was (1) to evaluate the compliance to SERM medication in postmenopausal women with osteoporosis; and (2) to determine the risk of osteoporotic fractures according to the compliance or other patient characteristics, using the Korean National Health Insurance (KNHI) claims database.…”
Section: Introductionmentioning
confidence: 99%